The Book of Ecclesiastes as «axial» archetext of the baroque poetry - Sinilo, Galina V. (Journal of the Belarusian State University. Philology, 2019)
The paper examines the role of the biblical Book of Ecclesiastes as one of the «axial» archetexts of the Baroque period and the most important meaning-generating text of the European Baroque poetry. It is shown how the key ideas, paradoxes and antinomies of existence and consciousness determine religious and philosophical discourse and literary world of Ecclesiastes; and how they affect the aesthetics and the poetics of the Baroque. It reveals in the basic philosophical principles and topics of the Baroque (vanitas mundi, discordia concors, Constantia) and in the paradoxical combination of tragic nature of life and glorification of its joy, pessimism and hedonism, skepticism and deep faith in persistence of human spirit finding support in God at the same time. Religious and philosophical poetry of the Baroque is associated with sustainable inter-, para- and architxtual connections and simultaneously it acts like a kind of detailed side note commentary of the biblical book, like metatext in relation to it. The constant dialogue with Ecclesiastes is typical for all European literatures of the XVII century but it is especially intensively developed in German poetry, due to the tragic German reality of the Early Modern Age.